ACCESS TO HEALTHY FOOD AND ADULT OBESITY: A SECONDARY SYNTHESIS OF EVIDENCE WITH CLINICAL IMPLICATIONS FOR ENDOCRINOLOGY - Milić, Marko Kimi; Sinanović, Šćepan; Kostić, Dejan; Ralić, Branislav; Gegić, Altan (Medical Gazzette, 2026)
Background: Obesity is highly prevalent and determined, in addition to individual factors, by characteristics of the food environment. Understanding how access to healthy food affects obesity risk is important for endocrinology.Objective: To summarize the relationship between access to healthy food and adult obesity and to highlight clinical and public health implications.Methods: A focused secondary synthesis based on a contemporary systematic review and meta-analysis, complemented by representative observational studies. Exposures were operationalized as proximity, density, and composite indices (e.g., RFEI). Pooled odds ratios (OR) with 95% confidence intervals were extracted; no new re–meta-analysis was performed. Quality and bias were considered within PRISMA and ROBINS-I domains.Results: It is consistently observed that closer access to fast food is associated with higher odds of obesity (≈OR 1.15), whereas proximity to supermarkets and higher density of fresh produce stores are associated with lower odds (≈OR 0.90 and ≈OR 0.93). Composite indices are more often near a neutral effect. Heterogeneity depends on the definition of the exposure zone (signal clearer in wider buffers, e.g., 1.5–3 kilometers) and on socioeconomic conditions. Although effects are moderate at the individual level, they can be clinically significant at the population level.Conclusion: Spatial access to healthy food is measurably associated with obesity risk. Endocrine practice should combine individual counseling with “mapping” local sources of fresh foods and referring patients to realistically available resources. Public policies that reduce the dominance of unhealthy offerings and encourage opening/sustainability of outlets with healthier foods have the potential for meaningful population benefit. Standardization of exposure metrics and evaluation of interventions in real-world settings are needed.
Keywords: obesity; food environment; proximity; density; supermarkets; fast food; endocrinology; public health.